2024
DOI: 10.24084/repqj10.716
|View full text |Cite
|
Sign up to set email alerts
|

Investigating two configurations of a heat exchanger in an Indirect Heating Integrated Collector Storage Solar Water Heating System (IHICSSWHS)

Abstract: Due to the environmental impact of energy usage and increased price of fusel fuel, consumers need to be encouraged to use renewable energy sources. The IHISSWHS (indirect heating integrated collector storage solar water heater system) is one of the most economical systems. It incorporates the collection of a solar energy component and a hot water storage component in one unit. The objective of this study was to investigate ways to enhance the thermal performance of the system. Two configurations of the system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…These discrepancies may be due to the oversimplification of the collector particularly inside the air gap of the panel. The researchers [40] performed the investigation using different configuration of inside flat plate integrated collector solar water heater systems. The inside flat plate integrated collector solar water heater system was configured having single and double rows inside it.…”
Section: Numerical Studies On Sfpcmentioning
confidence: 99%
“…These discrepancies may be due to the oversimplification of the collector particularly inside the air gap of the panel. The researchers [40] performed the investigation using different configuration of inside flat plate integrated collector solar water heater systems. The inside flat plate integrated collector solar water heater system was configured having single and double rows inside it.…”
Section: Numerical Studies On Sfpcmentioning
confidence: 99%
“…The optimum diameter was found to be 16 mm and they found that there is no need for a further increase in the tube length of 21.68 m in their system. Mossad and AL-Khaffajy [16] investigated two configurations of the heat exchanger in an indirect heating flat plate collector without circulating pump. They concluded that both the initial and running cost of the system could be minimized by using a single row heat exchanger touching the top wall of the tank.…”
Section: Introductionmentioning
confidence: 99%